2005
DOI: 10.1002/zaac.200500201
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Complexes of 2,2′‐Bidipyrrins

Abstract: The reaction of [{Ir(cod)(μ‐Cl)}2] and K2CO3 or of [{Ir(cod)(μ‐OMe)}2] alone with the non‐natural tetrapyrrole 2,2′‐bidipyrrin (H2BDP) yields, depending on the stoichiometry, the mononuclear complex [Ir(cod)(HBDP)] or the homodinuclear complex [{Ir(cod)}2(BDP)]. Both complexes react readily with carbon monoxide to yield the species [Ir(CO)2(HBDP)] and [{Ir(CO)2}2(BDP)], respectively. The results from NMR spectroscopy and X‐ray diffraction reveal different conformations for the tetrapyrrolic ligand in both comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The preparation of a series of earlier transition metal ion complexes expanded the list of known coordination geometries available to bis(dipyrrin)s. 91,184,240,241 A rhodium(I) cluster complex (4, shown previously in Figure 7) is the only example of non-κ 2 bonding of a metal ion by a bis(dipyrrin). 91 This lead to an investigation which showed that the rhodium reagents used in the preparation of bis(dipyrrinato) rhodium complexes affected the structure of the product in terms of the metal-to-ligand ratio.…”
Section: Nonracemic Helical Bis(dipyrrinato) Metal Complexesmentioning
confidence: 93%
See 1 more Smart Citation
“…The preparation of a series of earlier transition metal ion complexes expanded the list of known coordination geometries available to bis(dipyrrin)s. 91,184,240,241 A rhodium(I) cluster complex (4, shown previously in Figure 7) is the only example of non-κ 2 bonding of a metal ion by a bis(dipyrrin). 91 This lead to an investigation which showed that the rhodium reagents used in the preparation of bis(dipyrrinato) rhodium complexes affected the structure of the product in terms of the metal-to-ligand ratio.…”
Section: Nonracemic Helical Bis(dipyrrinato) Metal Complexesmentioning
confidence: 93%
“…The preparation of a series of earlier transition metal ion complexes expanded the list of known coordination geometries available to bis(dipyrrin)s. ,,, A rhodium(I) cluster complex ( 4 , shown previously in Figure ) is the only example of non-κ 2 bonding of a metal ion by a bis(dipyrrin) .…”
Section: 21 Nonracemic Helical Bis(dipyrrinato) Metal Complexesmentioning
confidence: 99%
“…[26][27][28] A substitution of hydrogen atoms for any other group at these positions would directly enhance the intramolecular repulsion and, therefore, the lability in complexes of such tetrapyrroles. 2,2'-Bidipyrrin compounds have been explored before as nitrogen-containing ligands in a number of mono-and dinuclear transition-metal chelates, [17,20,22,24,25,29,30] and the propensity of the terminal positions for chemical transformations has occasionally been documented. [31][32][33][34] Stable iron chelates, such as 2, can indeed be obtained from these ligands (Scheme 1), and we report herein the preparation, structure, spectroscopic analysis, and biomimetic reactivity of a unique series of iron 2,2'-bidipyrrin complexes [FeX-A C H T U N G T R E N N U N G (bdp)] (X = F, Cl, Br, I).…”
Section: -A C H T U N G T R E N N U N G (Bdp)]mentioning
confidence: 99%
“…Not only do these reactions yield different metalation patterns on the ligand ( 34 , 35 , 36 ), but they also enable ring closure to closed‐chain tetrapyrroles (see earlier) [84] . The synthesis and behavior of iridium and ruthenium complexes is comparable [85–87] …”
Section: Reactionsmentioning
confidence: 99%
“…[84] The synthesis and behavior of iridium and ruthenium complexes is comparable. [85][86][87] Lastly, iron chelates of dipyrrins can easily be synthesized from a suspension of FeCl 2 and FeCl 3 in 1,4-dioxane. [88] Here, the iron is coorrdinated as Fe(III) with an additional axial ligand such as Cl À .…”
Section: Metalationmentioning
confidence: 99%